Trust Me, I'm Partially Right: Incremental Visualization Lets Analysts Explore Large Datasets Faster - Fisher, Danyel; Popov, Igor; Drucker, Steven; schraefel, mc (Proceedings of the 2012 Conference on Human Factors in Computing Systems (CHI 2012), 2012)
Queries over large scale (petabyte) data bases often mean waiting overnight for a result to come back. Scale costs time. Such time also means that potential avenues of exploration are ignored because the costs are perceived to be too high to run or even propose them. With sampleAction we have explored whether interaction techniques to present query results running over only incremental samples can be presented as sufficiently trustworthy for analysts both to make closer to real time decisions about their queries and to be more exploratory in their questions of the data. Our work with three teams of analysts suggests that we can indeed accelerate and open up the query process with such incremental visualizations.